Endothelial cell dysfunction in cardiac disease: driver or consequence? - Allbritton-King, Jules D.; García-Cardeña, Guillermo (Frontiers in Cell and Developmental Biology, 2023)
The vascular endothelium is a multifunctional cellular system which directly influences blood components and cells within the vessel wall in a given tissue. Importantly, this cellular interface undergoes critical phenotypic changes in response to various biochemical and hemodynamic stimuli, driving developmental and pathophysiological processes. Multiple studies have indicated a central role of the endothelium in the initiation, progression, and clinical outcomes of cardiac disease. In this review we synthesize the current understanding of endothelial function and dysfunction as mediators of the cardiomyocyte phenotype in the setting of distinct cardiac pathologies; outline existing in vivo and in vitro models where key features of endothelial cell dysfunction can be recapitulated; and discuss future directions for development of endothelium-targeted therapeutics for cardiac diseases with limited existing treatment options.